SUFFERING OF WOMAN IN THE POETRY OF ALFRED TENNYSON - SAAD, HAIDER LUAIBI (مجلة كلية التربية, 2021)
Woman was and stills the center of any family; consequently she is the center of the whole society. The social suffering of women was of different forms which varied from suppression in education to isolation, deprivation of love and market-marriage. Woman in all societies lived in hard circumstances and was yoked to enslavement to man's prejudice and proud feeling of superiority. Alfred Tennyson highlighted woman's torture and problems trying to get his people acquainted with such suffering and open his people's eyes and minds to the tragedy of woman's maltreatment. He used his poetry to exhibit his beliefs in such plights. This paper deals mainly with Tennyson's treatment of woman's issues. First, it gives a biographical sketch of Tennyson's life, emphasizing those incidents and situations that affected his outlook towards woman which he depicts in his poems that defend her issues in society. Of those poems are “The Princess”, “, “Mariana” and “The Lady of Shalott”. The paper casts a light on one of these poems which is "The Princess" and ends with a conclusion that brings the final findings of the study out where the reader can make use of Tennyson's ways of understanding and presenting woman's problems.
Keywords: SUFFERING